Long-term cultivation of a stable Methylocystis-dominated methanotrophic enrichment enabling tailored production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate). (December 2015) - Myung, Jaewook; Galega, Wakuna M.; Van Nostrand, Joy D.; Yuan, Tong; Zhou, Jizhong; Criddle, Craig S.
Highlights: A Methylocystis -dominated CH4 -fed enrichment enabled stable PHBV synthesis. Harvested cells incubated with both methane and valerate produced PHBV. Mol% 3HV in PHBV was controllable. CH4 oxidation drives valerate uptake. The fraction of CH4 oxidized increases with increased mol% 3HV. Abstract: Methane (CH4 ) is a readily available feedstock for production of polyhydroxyalkanoates (PHAs). The structure and PHA production capacity of a Methylocystis -dominated methanotrophic enrichment was stable in long-term operation (>175 days) when grown exponentially under non-aseptic conditions in fill-and-draw batch cultures with ammonium as nitrogen source. Cells harvested in the draw step were incubated in the absence of nitrogen with various combinations of CH4 and valerate to assess capacity for synthesis of poly(3-hydroxybutyrate) (P3HB) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). When fed CH4 alone, only P3HB was produced. When fed CH4 plus valerate, PHBV was synthesized. The mol% of 3-hydroxyvalerate (3HV) increased with added valerate. Oxidation of CH4 was required for valerate assimilation, and the fraction of CH4 oxidized increased with increased mol% 3HV. By separating PHA accumulation from cell replication, tailored PHA-rich biomass can be generated by addition of co-substrate, while retaining a large inoculum for the next cycle of cell division.